Systematic Literature Review: Metode Pembuatan Nasi Instan dan Potensinya dalam Upaya Pengembangan Olahan Nasi sebagai Kekayaan Gastronomi Nusantara - Annisa Noor Rachmawati; Hendri Gigih Saputro; Aulia Firmansyah (Yayasan Literasi Sains Indonesia, 2025)
Indonesia has a rich variety of traditional regional rice dishes that represent the nation’s culinary and gastronomic heritage. However, these dishes typically have a short shelf life, limiting their availability to local consumption only. One potential solution to address this issue is the development of instant rice. Various studies have explored the production of instant rice, highlighting its potential as a medium to preserve and promote traditional rice-based dishes. This study aims to systematically review the methods used in the production of instant rice and its potential in enhancing the value of Indonesian gastronomic heritage. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol across multiple databases, including Google Scholar, PubMed, ScienceDirect, and MDPI. A total of 19 scientific articles that met the inclusion criteria were analyzed using the Population, Intervention, Comparison, Outcome, and Study Design (PICOS) framework. The review revealed that the production process of instant rice generally involves soaking in a citric acid solution, washing, cooking, cooling, freezing, thawing, and drying using various techniques. Drying methods include cabinet drying, fluidized bed drying, freeze drying, and microwave drying, each with different temperature and time settings depending on the rice type and target moisture content. The development of instant rice based on traditional recipes—packaged in a modern and practical format without compromising authentic flavors—holds strong potential to promote Indonesian gastronomy and enhance its competitiveness in the global culinary tourism market.